Cultural Specific Language in Kirat Yaakthung Mundhum - Tumbahang, Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2019)
This article attempts to discuss the various forms of the Kiraat Yaakthung Mundhum language employed in the various ritualistic performances. It has applied the qualitative research design in which the study attempts to gather non-numerical data explicitly referring to the meanings, concepts, definitions, or characteristics. Written documents related to the Kirat Yaakthung Mundhum are not adequate for having the ideas about the linguistic variations because the Mundhum is mostly based on oral tradition of recitation. The Limbu priests locally known as 'Saambaas' recite the diverse forms of the Mundhum depending on types of rituals they are performing. Basing on the available voice records, empirical knowledge, and written Mundhum documents, the paper has been prepared. After the analysis, the study has revealed that the elements of ethnographies of communication play a crucial role to bring about the distinctiveness in the level and meaning of the Mundhum utterances. This study may be helpful for those who are interested in the structure of the ritual language.